Pengaruh Konsentrasi Xanthan Gum Terhadap Sifat Fisikokimia dan Organoleptik Puree Nenas Beku - Rosalina Wijaya, T. Dwi Wibawa Budianta, Petrus Sri Naryanto, (Jurnal Teknologi Pangan dan Gizi, 2007)
One of the serious problem in the pineapple puree production is water drip of the pureee, so that detrimental effect on their sensory and water holding properties. The aim of the research is yo investigate the effect concentration xanthan gum on the physicochemical and sensory properties of frozen pineapple puree. The research used Block Randomized Design with single factor, i.e., the concentration xanthan gum (0%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%) The physichochemical properties (moisture, viscosity, drip, total soluble solid and color) and sensory properties (color, taste, mouthfeel, and flavor) of the product were determined. The result showed that concentration of xanthan gun affect the moisture, viscosity, drip, and color but did not affect total soluble solid frozen pineapple puree. At the concentration xanthan gum of 0.2% produced the best properties of frozen pineapple puree.